∫dxx(log⁡x)m is equal to

dxx(logx)m is equal to

  1. A

    (logx)mm+C

  2. B

    (logx)m1m1+C

  3. C

    (logx)1m1m+C

  4. D

    (logx)1mm+C

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

     Here, given integrand is not in any standard form. So,we convert it by substitution method in a standard form and then integrate it. 

    1x(logx)mdx Let  logx=t1x=dtdxdx=xdt1x(logx)mdx=1x(t)mxdt=tmdt=tm+1m+1+C=(logx)1m1m+C

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.